Simultaneous collision-induced transitions in H2O+CO2 gas mixtures. (July 2022) - Fleurbaey, H.; Mondelain, D.; Fakhardji, W.; Hartmann, J.M.; Campargue, A.
Highlights: Absorption spectra of CO2 +H2 O mixtures are measured by CRDS in the 1.6 µm window. A collision induced absorption (CIA) band is found to contribute to the continuum near 6000 cm −1 . The observed CIA is assigned to simultaneous excitations of CO2 and H2 O in the ν3 antisymmetric and ν1 symmetric stretching modes, respectively. The assignment is confirmed by the isotopic shift of the CIA in 13 CO2 +H2 O mixtures. Classical molecular dynamics simulations of the considered CIA agree with the observations. Abstract: A collision induced absorption (CIA) band has been measured near 6000 cm −1 in a spectrum of humidified CO2 recorded by cavity ring down spectroscopy (CRDS) at low pressure (<1 atm). This absorption adds a contribution to the H2 O+CO2 continuum mostly originating from far wings of the CO2 and H2 O resonance lines broadened by collisions with H2 O and with CO2, respectively. The observed CIA corresponds to a simultaneous excitation of 12 CO2 and H2 O colliding molecules in the ν3 antisymmetric and ν1 symmetric stretching mode, respectively. CRDS spectra recorded near 5940 cm −1 with a highly enriched 13 CO2 sample provide a confirmation of the assignment since the measured CIA isotopic spectral shift (of about −68 cm −1 ) coincides with that between the ν3 bands of 12 CO2 and 13 CO2 . The integrated binary coefficient of the two CIA is evaluated and found to be on the order of 2.3 × 10 −3  cm −2 amagat −2 . Classical molecular dynamics simulations (CMDS) of the considered CIA are also presented, based on the dominant dipole induction mechanism associated with the vibrational matrix elements of the dipole of CO2 (ν3 ) and isotropic polarizability of H2 O (ν1 ). The results of the calculations are found in good agreement with the observations, thus further validating the attribution of the observed CIA structure to the above mentioned double transitions. Graphical abstract: Image, graphical abstract